Ethnographic research on primary education of tribals: a scoping review - Mathew, Jemy Jose; Thomas, Kennedy Andrew (Journal of Education and Learning (EduLearn), 2026)
Ethnographic research offers comprehensive learning outcomes by examining the socio-emotional, economic and cultural components crucial for comprehending marginalized groups’ experiences. This study aims to examine the methodologies used in studies and the gaps in the literature on the primary education of tribal communities, highlighting the limitations of the current research approaches. Using the preferred reporting items for systematic reviews and meta-analyses (PRISMA) of Arksey and O’Malley’s six-step framework, the scoping review has considered 19 studies of 406 research articles published from 2015 to 2024 across the databases Scopus, JSTOR, and ERIC. The review highlights that most of these studies used descriptive survey design, mixed-method research design, and ethnographic research design. While the first two document barriers, the ethnographic studies provide richer cultural in-depth also. However, gaps in the literature include a lack of interventions for specific tribes, such as the Mannan community in Kerala, India, and the integration of indigenous knowledge, which is only possible through cultural inclusiveness. The findings suggest that future research should prioritize interdisciplinary collaboration and teacher training in multilingual education (MLE) through ethnographic methods for developing culturally sensitive interventions. These recommendations aim to contribute to developing more culturally inclusive educational practices and policies in the primary education curricula.